A Qualitative Investigation on Patient Empowerment in Prostate Cancer - Renzi, Chiara; Fioretti, Chiara; Oliveri, Serena; Mazzocco, Ketti; Zerini, Dario; Alessandro, Ombretta; Rojas, Damaris P.; Jereczek-Fossa, Barbara A.; Pravettoni, Gabriella (Frontiers in Psychology, 2017)
Purpose. eHealth interventions may represent useful tools to deliver care and education and to meet patients’ needs within an empowerment framework. In order to design a platform for cancer patients’empowerment within the H2020 iManageCancer project, the perspective of the target population for the platform was assessed as suggested by recent studies. Men with prostate cancer often describe low levels of empowerment. The present study aims to assess the qualitative experience of prostate cancer patients during treatment in order to provide insights for clinical practice with a particular focus on the design of a web platform to promote cancer patients’ empowerment. Methods. Ten patients undergoing radiation therapy treatment took part in a semi-structured interview to explore different aspects of patient empowerment. Four main thematic areas were addressed: patient-healthcare providers’ communication, decision-making, needs and resources. A qualitative approach using thematic analysis was followed. Results. Half of the patients reported a lack in the possibility to share information and questions with healthcare providers. For decision-making, the role of healthcare providers was perceived as directive/informative, but half of the patients perceived to assume an active role in at least one interaction. Difficulties and needs included the choice of specialist or of the structure after diagnosis, clinicians’ support in self-management, surgical consequences and side effects, preparation for radiation therapy. Resources included family and social support both from a practical and from an emotional perspective, coping style, and work schedule management. Conclusions. These results suggest that relations with healthcare providers should be supported, especially immediately after diagnosis and after surgery. Support to self-management after surgery and at the beginning of radiation therapy treatment also constitutes a priority. The adoption of a personalized approach from the beginning of prostate cancer care flow may promote patient empowerment, overcoming the aforementioned needs and mobilizing resources. The social network represents an important resource that could be integrated in interventions. These considerations will be taken into account in the design of a cancer self-management platform aiming to increase patients’ empowerment.